Pengaruh Tourism Product Attributes Terhadap Tourist Satisfaction di Desa Wisata Kertayasa Kabupaten Pangandaran - Tias, Audinna; Waluya, Bagja; Khaerani, Rijal (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2022)
Satisfaction is a crucial factor to success in the tourism business. The problem encountered by Kertayasa tourism village of Pangandaran regency is tourist dissatisfaction. Therefore, a strategy of tourism product attributes can increase tourist satisfaction. This study aims to determine the effect of tourism product attributes on tourist satisfaction. The type of research uses descriptive and verification, using an explanatory survey with a cross-sectional-method approach. The data were analysed using multiple linear regression. The sampling technique used purposive sampling, 135 tourists who had visited the Kertayasa tourism village of Pangandaran regency. The results showed that simultaneous and partial variables of tourism product attributes affect tourist satisfaction. The result of this study discloses that the dimension of attractions/experiences has the most impact on the rise of tourist satisfaction. The findings of this study are expected to advice the manager of Kertayasa tourism village in making a policy regarding the development of marketing strategies by improving the quality of tourism product attributes to increase tourist satisfaction.